Hubungan Asertivitas dengan Kepuasan Pernikahan pada Pasangan Suami Istri Yang Bekerja - Anggraeni, Riananda Sevania (Universitas Muhammadiyah Metro, 2023)
A couple's feelings of participation in various facets of their unique married life are referred to as their marital pleasure. Communication is one of the variables that might influence marital satisfaction; husband and wife need to have the confidence to express feelings and opinions in an open, honest manner, which is referred to as assertiveness. The purpose of this study is to ascertain how assertiveness and marital satisfaction relate to working men and spouses. Quantitative study with a correlational design was used. The incidental sampling method was utilized in this study, which had 202 participants in total. The Rathus Assertiveness Scale (RAS) and the ENRICH Marital Satisfaction (EMS) Measure were employed as the research measuring tools (both scores of 0.893 and 0.814). Spearman's rank correlation was the analysis method employed, and the analysis's findings showed a correlation coefficient of 0.443.According to the findings, assertiveness and marital satisfaction are significantly positively correlated in working husbands and spouses. Couples that have the guts to communicate their wants and opinions honestly, strongly, and with respect rather than by being combative or defensive will typically report higher levels of marital satisfaction.